The Instrument as Instrumental: Pgaz k’Nyau Bamboo Musicking and Karen Eco-Friendliness - Phattanaphraiwan, Suwichan "Chi"; Fairfield, Benjamin Stuart (Malaysian Journal of Music, 2019)
While the tehnaku, the iconic six-string curved neck harp of the Pgaz k’Nyau (Sgaw Karen) people has made a strong comeback after 19th and 20th century, scholars lamented its demise, many other traditional bamboo instruments of the Pgaz k’Nyau still remain little-known, not only in academia but increasingly within Pgaz k’Nyau communities themselves, due in part to national forestry laws, resettlement and evictions, modernisation campaigns, and an increasing scarcity of, or restricted access to, certain natural and cultural resources. This ethnographic study investigates the various uses of bamboo in two Pgaz k’Nyau communities in Thailand, illustrating the importance of local knowledge of natural resources and the place of bamboo in shaping Pgaz k’Nyau music, ethics, aesthetics, ecological activity, beliefs and social relations. Bamboo musical instruments, in legends and in everyday application, are co-created with help from rodents and insects, lure wild pigs from the forest, bookend human lifecycles, help to confine spirits to the forest and the afterlife and are reworked from pig troughs into slit-drums used to drum up communal action. This research discusses how these increasingly rare bamboo musical instruments speak to a variety of contemporary contextual issues faced in Pgaz k’Nyau communities. We argue that Pgaz k’Nyau bamboo is instrumental in reflecting and perpetuating long-standing eco-friendly cultural practices embodied in a five-part Pgaz k’Nyau prescription for managing ecological relations within the self, between self and other, between the human and animal world, between human and forest, and between human society and the supernatural world; and it does so in response to Thai political narratives that have inappropriately labelled the Pgaz k’Nyau as destroyers of national forests.